2004
DOI: 10.1074/jbc.m405189200
|View full text |Cite
|
Sign up to set email alerts
|

Spred-1 Negatively Regulates Interleukin-3-mediated ERK/Mitogen-activated Protein (MAP) Kinase Activation in Hematopoietic Cells

Abstract: Sprouty/Spred family proteins have been identified as negative regulators of growth factor-induced ERK/mitogen-activated protein (MAP) kinase activation. However, it has not been clarified whether these proteins regulate cytokine-induced ERK activity. We found that Spred-1 is highly expressed in interleukin-3 (IL-3)-dependent hematopoietic cell lines and bone marrow-derived mast cells. To investigate the roles of Spred-1 in hematopoiesis, we expressed wild-type Spred-1 and a dominant negative form of Spred-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
105
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 46 publications
(54 reference statements)
2
105
0
1
Order By: Relevance
“…The kinase activity of ERK is fully activated through the phosphorylation of threonine (Thr 202) and tyrosine (Tyr 204) of ERK by MAP kinase kinase (MEK), which is activated by Raf. Recently, we reported that Spred-deficient cells showed increased cell proliferation with enhanced phosphorylation of ERK (Nonami et al, 2004). These findings suggest that the expression of Spred may have a profound effect on cell proliferation by regulating ERK activity.…”
Section: Discussionmentioning
confidence: 87%
“…The kinase activity of ERK is fully activated through the phosphorylation of threonine (Thr 202) and tyrosine (Tyr 204) of ERK by MAP kinase kinase (MEK), which is activated by Raf. Recently, we reported that Spred-deficient cells showed increased cell proliferation with enhanced phosphorylation of ERK (Nonami et al, 2004). These findings suggest that the expression of Spred may have a profound effect on cell proliferation by regulating ERK activity.…”
Section: Discussionmentioning
confidence: 87%
“…In line with these in vitro data, we detected higher CRH mRNA contents in hypothalami of KO mice, paralleled by an increased CRH secretion. Because the suppressive effect of SPRED2 is restricted to the MAPK pathway (23)(24)(25), it seems reasonable that the up-regulated MAPK signaling in our KO mice probably leads to an augmented ERK/ Ets-dependent CRH transcription and release, resulting in an overproduction of hormones at all levels of the HPA axis.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that EVH1 domains of SPREDs act dominant negative (25), but for an efficient suppression of MAPK signaling, both the EVH1 and the SPR domains seem to be required (24). This led us to the assumption that the aberrant expression of EVH1-␤-geo does not affect the MAPK-dependent regulation of the HPA axis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations